Framing strategic storytelling in the context of transition management to stimulate tourism destination development. (December 2019) - Hartman, Stefan; Parra, Constanza; de Roo, Gert
Abstract: This article frames strategic storytelling in the context of transition management in order to analyse how strategic applications of storytelling stimulate destination development. This analytical framework is applied to two cases of storytelling projects aimed at fostering the destination development of the regions Hondsrug and Friese Meren, the Netherlands. We discuss how considering destination development as a long-term spatial transformation process (transition) and adopting a multilevel perspective (MLP) allows 1.) to pinpoint how strategic storytelling contributes to regional development and 2.) to identify factors that positively and negatively influence this contribution. We conclude that using storytelling in the context of transitions benefits from an adaptive approach of continually evaluating and adjusting actions – including storytelling. This allows for reinforcing existing ties and establishing new ties between actors so to effectively mobilise and unite public and private actors on multiple governance levels and result in actions that contribute to destination development. Highlights: The article analyses how strategic applications of storytelling (SST) stimulate destination development. Using strategic storytelling (STT) to stimulate the long term transition of destinations requires an adaptive approach. Storytelling can make valuable contributions to destination development when applied in a strategic-adaptive manner. Strategic storytelling depends on initiators with the capacity to mobilise actors and resources for storytelling projects. In strategic storytelling stories create bridges and reinforce bonds between actors.